Baffle jetting: CFD analysis of plain jets impinging on fuel rods. (July 2019) - Bieder, Ulrich; Rashkovan, Alexander
Abstract: The risk of baffle jetting exists mainly in pressurized water reactors, which are designed with a counter flow configuration in the core bypass region. Baffle plates are foreseen between core barrel and core, providing the core's lateral restraint and allowing a core bypass flow. A pressure differential establishes between the coolant flow in the core baffle and the upward flow through the core. A part of the coolant bypass flow is directed through the gaps of the baffle plates towards the core. Coolant cross flow through enlarged baffle gaps can result in high velocity jetting in the case of significant pressure differences between core and baffle region. These water jets impact onto the fuel rods and may induce rod vibration that can lead to fuel rod failure. Modelling baffle jetting induced vibrations of fuel rods is still a challenge in the field of fluid structure interaction. The present work aims to extend the understanding of the unsteady flow in rod bundles to situations where baffle jetting occurs. As a first step, the used LES modelling method is evaluated on the example of a well documented test case related to fuel rods in cross flow: the flow over a circular cylinder at Re  = 3900. In the successive step, the validated modelling method is applied to the CEA PANACHET experiment, mimicking baffle jetting related phenomena. This analysis helped to understand better the flow field of a corner baffle jet and further validated the modelling approach. The flow field in the core baffle corner is finally analysed for realistic reactor conditions. A plain narrow slot jet is injected parallel to a baffle wall through a 1 mm width gap perpendicular to the axial flow of a corner assembly. The analysis of the flow field showed that: (i) Swirling flow exist close to the corner rod. The calculated force coefficients lift and drag of this rod show a dominant fluctuation frequency of about 80 Hz. (ii) The baffle jet impacts on the third rod in jet direction (passing the first two rods without impact). The force coefficients of the third rod do not show a dominant oscillation frequency but show increased oscillation amplitudes. The distinguished fluctuation frequency detected for rod n°1 and the direct impact of the baffle jet on rod n°3 might explain the rod failures that have been detected for these rods. Highlights: Baffle jetting can be responsible for fuel rod damage in PWR . Baffle jetting is analysed by CFD using LES . Cylinder in cross flow and PANACHET experiments serve as validation cases . Lift and drag coefficients of corner fuel rods are calculated . The possible failure of the first and third rod in baffle jet direction is explained .